2019
DOI: 10.1590/s0004-2803.201900000-03
|View full text |Cite|
|
Sign up to set email alerts
|

[Article Partial Retraction] Prevalence of Helicobacter Pylori Infection in Dyspeptic Patients and Its Association With Clinical Risk Factors for Developing Gastric Adenocarcinoma

Abstract: BACKGROUND: In Brazil, particularly in the underdeveloped localities, the prevalence of Helicobacter pylori (H. pylori) infections can range up to 90%. These rates are higher in older individuals and vary by country region. H. pylori infections are linked to the development of gastric pathologies, namely mild to moderate gastritis, gastroenteritis, peptic ulcer, intestinal metaplasia, and gastric cancer. In 1994, this organism was classified by the International Agency for Research on Cancer (IARC) as pertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
3
0
3
Order By: Relevance
“…The data were confirmed by multivariate logistic regression analysis. Similar results of other studies revealed that H. pylori infection was associated with dyspepsia (Misganaw and Abera, 2017;Tameshkel et al, 2018;Borges et al, 2019;Mabeku et al, 2020). Other study showed the predictor of seroprevalence H. pylori was found to be epigastric pain (Hamrah et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…The data were confirmed by multivariate logistic regression analysis. Similar results of other studies revealed that H. pylori infection was associated with dyspepsia (Misganaw and Abera, 2017;Tameshkel et al, 2018;Borges et al, 2019;Mabeku et al, 2020). Other study showed the predictor of seroprevalence H. pylori was found to be epigastric pain (Hamrah et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Several of the risk factors in this study were associated with increased odds of GIM. H. pylori, a carcinogen, is strongly associated with GIM [15,[25][26][27][28][29][30]. There was a higher percentage of GIM with H. pylori infection (14.4% vs. 5.6%) in this study.…”
Section: Discussionmentioning
confidence: 43%
“… 2 In Brazil, the prevalence is heterogeneous in different regions, with proportions of 31.7%, 61.1%, and 91% in the Southeast, Midwest, and North regions, respectively. 3 , 4 , 6 The prevalence of infection depends on different factors, and it is necessary to consider that these values may have been influenced by the living conditions of the population, different diagnostic methods, genetic characteristics of patients and bacteria, and lifestyle habits, among others.…”
Section: Discussionmentioning
confidence: 99%